Diabetic polyneuropathy is associated with pathomorphological changes in human dorsal root ganglia: a study using 3T MR neurography - Jende, Johann; Kender, Zoltán; Rother, Christian; Alvarez-Ramos, Lucia; Gröner, Jan; Pham, Mirko; Morgenstern, Jakob; Oikonomou, Dimitrios; Hahn, Artur; Jürchott, Alexander; Hayes, Jennifer; Heiland, Sabine; et al. (Frontiers in neuroscience, 2020)
Diabetic neuropathy (DPN) is one of the most severe and yet most poorly understood complications of diabetes mellitus. In vivo imaging of dorsal root ganglia (DRG), a key structure for the understanding of DPN, has been restricted to animal studies. These have shown a correlation of decreased DRG volume with neuropathic symptom severity. Our objective was to investigate correlations of DRG morphology and signal characteristics at 3 Tesla (3T) magnetic resonance neurography (MRN) with clinical and serological data in diabetic patients with and without DPN. In this cross-sectional study, participants underwent 3T MRN of both L5 DRG using an isotropic 3D T2-weighted, fat-suppressed sequence with subsequent segmentation of DRG volume and analysis of normalized signal properties. Overall, 55 diabetes patients (669 years; 32 men; 30 with DPN) took part in this study. DRG volume was smaller in patients with severe DPN when compared to patients with mild or moderate DPN (134.721.86 vs. 170.149.22; p=0.040). In DPN patients, DRG volume was negatively correlated with the neuropathy disability score (r=-0.43; 95%CI=-0.66 to -0.14; p=0.02), a measure of neuropathy severity. DRG volume showed negative correlations with triglycerides (r=-0.40; 95%CI=-0.57 to -0.19; p=0.006), and LDL cholesterol (r=-0.33; 95%CI=-0.51 to -0.11; p=0.04). There was a strong positive correlation of normalized MR signal intensity (SI) with the neuropathy symptom score in the subgroup of patients with painful DPN (r=0.80; 95%CI=0.46 to 0.93; p=0.005). DRG SI was positively correlated with HbA1c levels (r=0.30; 95%CI=0.09 to 0.50; p=0.03) and the triglyceride/HDL ratio (r=0.40; 95%CI=0.19 to 0.57; p=0.007). In this first in vivo study, we found DRG morphological degeneration and signal increase in correlation with neuropathy severity. This elucidates the potential importance of MR-based DRG assessments in studying structural and functional changes in DPN.
Gesehen am 10.11.2020